Kebijakan Insentif Pajak UMKM Di Masa Pandemi Covid -19 - Asadi Asadi; Hermi Sularsih; Sukarno Himawan Wibisono; Ahmad Mukoffi (e-Journal Perdagangan Industri dan Moneter, 2022)
This study aims to determine the MSME tax incentive policy during the Covid-19 pandemic at KPP Pratama Pasuruan. This research method is carried out qualitatively. The use of data in this research is based on interviews with tax officer. Data analysis in this research is explanatory or descriptive. The research finding that the MSME tax incentive policy during the Covid-19 pandemic at KPP Pratama Pasuruan was considered to help MSME business actors to reduce the amount of tax payable and increase the amount of local tax revenue. The tax incentive policy is regulated in PMK number 44/PMK.03/2020, by providing MSME tax incentives from 1 percent to 0.5 percent. Taxpayers are expected to take advantage of tax incentives so that they are more obedient in paying taxes to support Pasuruan tax revenues.